Mindanao healing the past, building the future - Chiu, Stella; Nolasco, Butch; Rodrigo, Raul (Bookmark, 1990)
A documentary on the history of the on-going conflict between Christian and Muslim Filipinos in Mindanao, and how some individuals and institutions have found a way to build a culture of mutual respect, tolerance and openness, thus demonstrating that peace is possible in Mindanao.